Analysis of Additional Employee Income Provisions in Improve Employee Performance at The Ulunoyo District Office South Nias Regency - Ndruru, Rainelda Rosalia; Zega, Yamolala; Telaumbanua, Eliagus; Waruwu, Sukaaro (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study analyzes the provision of Additional Employee Income (Tambahan Penghasilan Pegawai/TPP) in enhancing employee performance at the Ulunoyo Subdistrict Office, South Nias Regency. The research is motivated by the phenomenon that, despite the implementation of TPP, some employees still show low discipline, absenteeism, and lack of service quality. The study employs a qualitative approach with data obtained through interviews, observation, and documentation involving key informants such as the subdistrict head, secretary, section chiefs, and staff members. The findings reveal that the TPP policy has a positive impact on employee motivation and performance; however, its implementation faces several challenges, including weak discipline, low awareness of responsibilities, and limited supervisory mechanisms. The results suggest that the effectiveness of TPP depends not only on financial incentives but also on non-financial factors such as leadership, work environment, and employee commitment. Strengthening monitoring, improving employee discipline, and ensuring fair distribution of incentives are necessary to optimize performance outcomes. This research contributes to the discourse on public sector human resource management and provides insights for local governments in enhancing bureaucratic performance.